Public Perception on Corrupt Practices in Nigeria's Fourth Republic: A Study of Ogun State, Nigeria - Olapade, Olawale; Isola, Abidemi Abiola (NIU Journal of Humanities; Vol 6 No 2 (2021): KIU Journal of Humanities, Vol. 6 No. 2, June 2021, 2021)
Without mincing words, it remains an incontestable point of fact that Nigeria as a nation, which is greatly and bountifully endowed with natural resources and uncommon workforce is yet to find its rightful place among the comity of nations.  A major reason that has been responsible for her socio-economic stagnation is the phenomenon of corruption.  Corruption is a hydra-headed monster, which has eaten deep into the fabric of Nigeria, though, it is a global challenge that needs to be fought head-long collectively with the universal approach, but it seems to be more pronounced in Nigeria than elsewhere in the world.  What is worrisome therefore is the delicate and pernicious twist and dimension it takes in the present day Nigeria.  It is on this premise the researcher of this work centres this finding and contribution to knowledge around.  It is noteworthy, that the scope of this dissertation largely covers the menace of different forms of corruption and its implications, and the devastating effects of high profile corrupt practices on Nigeria's socio-economic and developmental growth, vis-Ã -vis the general public perception of corruption in Nigeria: A Case study of Ogun State, in the South-West of the Country.  This research work also recognizes the fact that political leadership and corruption are synonymous in Nigeria's context today, as they are inextricably intertwined and inseparable in the contemporary Nigerian democratic governance.  By way of submission, this work draws an inference that for Nigeria to have a sustainable socio-economic development, a responsive, responsible, credible and selfless political leadership must come on board to truly adopt a God-centred approach in politics, instill an act of discipline, societal and moral values in the citizenry of this country. Selfless services and good governance with the tenacity and sincerity of purpose should be its golden rules and watchword in piloting the affairs of this great nation, called Nigeria. Keywords: Corrupt Practices, Public Behaviour